2000
DOI: 10.1093/oxfordjournals.bja.a013478
|View full text |Cite
|
Sign up to set email alerts
|

Malignant hyperthermia in infancy and identification of novel RYR1 mutation

Abstract: Malignant hyperthermia (MH) has been reported as non-existent in children less than 1 yr old, although several unconfirmed reports have been published. A case report of MH in a 6-month-old child is presented, with confirmation of MH susceptibility by in vitro contracture testing of quadriceps muscle at 13 yr old. Genetic analysis revealed a novel RYR1 mutation that substitutes arginine 2452 for tryptophan in a region of the calcium channel mutated in several other MH pedigrees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 5 publications
0
23
0
Order By: Relevance
“…It has been found that children under 15 years age comprised 52.1% of all reactions. Although described in the newborn, the earliest reaction confirmed by testing is six months of age [2]. The oldest is 78 years.…”
Section: Epidemiologymentioning
confidence: 99%
“…It has been found that children under 15 years age comprised 52.1% of all reactions. Although described in the newborn, the earliest reaction confirmed by testing is six months of age [2]. The oldest is 78 years.…”
Section: Epidemiologymentioning
confidence: 99%
“…The research approach included clinical diagnosis as well as molecular genetic analysis of DNA collected from individuals of families known to be susceptible to MH. The major thrust of the project was focused on Whanau Rua, and the research confirmed that affected members of the whanau carry a specific gene mutation that does not occur in the general population Chamley et al 2000;MidCentral 2007). Six members of Whanau Rua were interviewed for this study, and they all have personal experience of genetic testing and associated decision making.…”
Section: Whanau Ruamentioning
confidence: 94%
“…Children and young adults are mostly affected, with a significant male preponderance 7,13,14. According to a prevalence study in New York State between 2001 and 2005, the estimated prevalence of MH was 2.5–4.5 times higher in males than in females 15.…”
Section: Epidemiologymentioning
confidence: 99%